Superresolution microscopy reveals partial preassembly and subsequent bending of the clathrin coat during endocytosis - Mund, Markus; Tschanz, Aline; Wu, Yu-Le; Frey, Felix; Mehl, Johanna L.; Kaksonen, Marko; Avinoam, Ori; Schwarz, Ulrich S.; Ries, Jonas (bioRxiv beta, 2021)
Eukaryotic cells use clathrin-mediated endocytosis to take up a large range of extracellular cargos. During endocytosis, a clathrin coat forms on the plasma membrane, but it remains controversial when and how it is remodeled into a spherical vesicle. - Here, we use 3D superresolution microscopy to determine the precise geometry of the clathrin coat at endocytic sites. Through pseudo-temporal sorting, we determine the average trajectory of clathrin remodeling during endocytosis and find that clathrin coats assemble first on flat membranes to ≈50% of the coat area, before they become rapidly and continuously bent. We introduce a mathematical model that assumes a positive feedback for curvature generation of the clathrin coat. The cooperative curvature model agrees excellently with experimental data in three cell lines, and likely describes a general pathway for clathrin coat remodeling during endocytosis.
Gesehen am 09.11.2022